The Secret Life of Tethers: The Role of Tethering Factors in SNARE Complex Regulation - Dubuke, Michelle L.; Munson, Mary (Frontiers in Cell and Developmental Biology, 2016)
Trafficking in eukaryotic cells is a tightly regulated process to ensure correct cargo delivery to the proper destination organelle or plasma membrane. In this review, we focus on how the vesicle fusion machinery, the SNARE complex, is regulated by the interplay of the multisubunit tethering complexes (MTC) with the SNAREs and Sec1/Munc18 (SM) proteins. Although these factors are used in different stages of membrane trafficking, e.g. Golgi to plasma membrane transport vs vacuolar fusion, and in a variety of diverse eukaryotic cell types, many commonalities between their functions are being revealed. We explore the various protein-protein interactions and findings from functional reconstitution studies in order to highlight both their common features and the differences in their modes of regulation. These studies serve as a starting point for mechanistic explorations in other systems.